2012
DOI: 10.1007/s10067-011-1929-5
|View full text |Cite
|
Sign up to set email alerts
|

Parenting: the forgotten role of women living with systemic lupus erythematosus

Abstract: This study investigates parenting and the impact of symptoms, such as pain and fatigue, on the parenting abilities of mothers with systemic lupus erythematosus (SLE). Participants were 68 mothers with SLE who had children 18 years of age and younger. The mothers completed surveys consisting of a demographic questionnaire and self-report instruments such as the Parenting Disability Index (PDI), Health Assessment Questionnaire, Pain Visual Analog Scale, and Multidimensional Assessment of Fatigue Scale. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
2
16
0
1
Order By: Relevance
“…However, in our study women reported a particularly high impact of their disease on work (role domain mean 7.79, SD 3.0). Functional disability and fatigue have previously been identified as having an impact on the parenting roles of women with Systemic Lupus Erythematous [37]. Women with Rheumatoid Arthritis also report that pain and fatigue impacts on their parenting roles [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study women reported a particularly high impact of their disease on work (role domain mean 7.79, SD 3.0). Functional disability and fatigue have previously been identified as having an impact on the parenting roles of women with Systemic Lupus Erythematous [37]. Women with Rheumatoid Arthritis also report that pain and fatigue impacts on their parenting roles [38].…”
Section: Discussionmentioning
confidence: 99%
“…Related to the finding of age as being significantly related to elevated HAQ score in SLE patients, Poole et al [ 51 ] recently found activity limitation to be pronounced in younger parenting females with SLE. Mothers with small children (<5 years) reported that having energy to talk/listen to a child was the most difficult parenting task.…”
Section: Discussionmentioning
confidence: 99%
“…Even the role of parenting may be affected. Poole et al [20] showed that symptoms from SLE influenced women's parenting roles, due to a lack of energy to talk and listen to a child, difficulties with maintaining discipline, playing games, shopping and doing household chores. Contrastingly, there were patients who reported positive impacts of the disease, such as it bringing the family closer together [18] and being a legal reason to leave a job they did not like [16].…”
Section: Systemic Lupus Erythematosus and Impact On Lifementioning
confidence: 99%